2017
DOI: 10.1302/2058-5241.2.160036
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of acetabular fractures in the elderly: a systematic review of the results

Abstract: We performed a systematic review of the literature involving a number of databases to identify studies that included outcomes of surgical treatment of acetabular fractures in patients aged > 55 years. An initial search identified 1564 studies. After exclusion by two independent reviewers, 15 studies met the inclusion criteria. All studies were case series and the mean Coleman Methodology score for methodological quality assessment was 43.7 (standard deviation 12.3). There were 354 patients with acetabular frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 34 publications
6
53
1
1
Order By: Relevance
“…The papers included in the review are reported by category in Table 2. Bone grafting techniques have a major role in several orthopedic and trauma procedures in which bone augmentation and regeneration is needed [12]. Autologous bone graft (ABG) combines all properties required for a biological graft: osteogenic, osteoconductive and osteoinductive properties.…”
Section: Resultsmentioning
confidence: 99%
“…The papers included in the review are reported by category in Table 2. Bone grafting techniques have a major role in several orthopedic and trauma procedures in which bone augmentation and regeneration is needed [12]. Autologous bone graft (ABG) combines all properties required for a biological graft: osteogenic, osteoconductive and osteoinductive properties.…”
Section: Resultsmentioning
confidence: 99%
“…Periprosthetic joint infections represent one of the most common complication following joint arthroplasty, both after primary or revision surgery [18][19][20][21]. However tubercular PJI is a rare clinical condition in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of periprosthetic acetabular fractures represents a challenging issue for the orthopedic surgeon who has to address both the need for fracture reduction and stability, and an effective joint reconstruction [19,23]. Periprosthetic acetabular fractures often occur in patients in which poor bone quality is often concomitant with periprosthetic bone lysis [2]. CT scan, with MAR protocol, represents the preferred diagnostic method for the evaluation of periprosthetic acetabular fractures and the quantification of periprosthetic bone loss [6].…”
Section: Discussionmentioning
confidence: 99%
“…Such fractures represent 3.8% of hip revisions, but the number will grow due to a progressive increase in primary hip implants [1]. Therefore, particularly in elderly and fragile patients, these fractures are associated with aseptic loosening, periprosthetic osteolysis and severe bone loss [2].…”
Section: Introductionmentioning
confidence: 99%